PENDIDIKAN ISLAM SEBAGAI PILAR PEMBANGUNAN BERKELANJUTAN: PERAN SISTEM PENDIDIKAN PESANTREN DALAM IMPLEMENTASI SDGs - Asdlori Asdlori (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2023)
This study aims to examine the role of the pesantren education system in the implementation of Sustainable Development Goals (SDGs) and make Islamic education a pillar of sustainable development. The research background includes the importance of integrating religious education with sustainable development goals in order to create a just, sustainable, and prosperous society.  The research method used is a qualitative approach by conducting a case study at the Al Hidayah Karangsuci Islamic Boarding School, Purwokerto, Central Java. Data are obtained through observation, interviews, and document analysis. The results showed that thepesantren education system is integrated with Islamic values and SDGs principles, producing students who have complete personalities, akhlakul karimah, and maturity of Ahlussunnah wal Jama'ah creed. In the context of SDGs implementation, the pesantren education system plays an important role by integrating the goals and principles of SDGs in the curriculum and educational activities.  The conclusion shows that Islamic education in the  pesantren education system has a strategic role in achieving SDGs and forming a just, sustainable, and prosperous society